Substrate reduction therapy with miglustat for type 1 Gaucher disease: A retrospective analysis from a single institution - Machaczka, Maciej (Informa Healthcare, 2012)
INTRODUCTION. Gaucher disease (GD) is an infrequent progressive multisystem lysosomal storage disorder caused by the deficient activity of the lysosomal enzyme, glucocerebrosidase. A retrospective, single-center analysis of the clinical experience concerning the use of miglustat (N-butyldeoxynojirimycin), an oral inhibitor of glucosylceramide synthase, in type 1 Gaucher disease (GD1) was conducted to evaluate the efficacy, adverse events (AE), and outcome of miglustat therapy. PATIENTS AND METHODS. Six adult Caucasian patients with GD1 (two women and four men), aged 21–81 years (median age 59 years), were treated with miglustat between October 2005 and April 2011. All but one patient (83%) carried at least one allele with c.1226A>G (N370S) mutation in the GBA1 gene. RESULTS. Weight loss, diarrhea, poor appetite, and tremor were frequently reported AE by the patients. All of them experienced at least 2 AE, and three patients (50%) experienced at least 4 AE. Only two out of six patients (33%) have used miglustat longer than 12 months, of which only one used it longer than 15 months. CONCLUSIONS. The major obstacle to successful miglustat therapy in GD1 was the high proportion of patients discontinuing their treatment due to the AE and the worsened quality of life. Further efforts are needed to improve tolerability of miglustat and, in consequence, compliance of patients treated with this orphan drug.